Body mass index and body composition with deuterium in Costa Rican Children - Eugenia Ma. Quintana-Guzmán; María del Pilar Salas-Cháves; Mayra Cartín-Brenes (Instituto Nacional de Pediatría, 2014)
Body Mass Index (BMI) has been adopted as international measure for measuring adiposity in children with the disadvantage that it varies with age, sex and sexual maturation with no differentiation between fat mass and mass free of grease. The analysis of body composition allow to know if the overweight is due to fatty tissue being the deuterium isotope dilution method a validated reference method using Infrared Spectrometry Transformed of Fourier (FTIR).